Epidendrum manusalinasiae (Orchidaceae: Laeliinae), new species from the high Andean forests of Manu National Park, Cusco, Perú - Alfaro, Lucero E.; Salinas, Julian Duarte; Hágsater, Eric; Cano, Asunción (Phytotaxa, 2024)
We describe and illustrate a new species of Epidendrum from the high Andean forests of Manu National Park, Cusco. Epidendrum manusalinasiae belongs the Saxicola group. Information on its distribution, habitat, phenology, and conservation status is provided. The new species is compared with E. churubambense, E. herreranum and E. tetartociclium from which it is distinguished by having leaves elliptic to widely elliptic, flowers pale yellow to green, sepals sometimes tinged red-brown, column and calli creamy yellow, lip disc with large, fleshy thickened, forming wide cordiform platform, wider than mid-lobe and reaching its base and mid-lobe whit distal portion plicated forward, whit a sub-lobed appearance in natural position.